Analisis Resepsi Khalayak Terhadap Pesan Iklan Layanan Masyarakat “Disinformasi” Covid 19 (Studi Pada Komunitas Mersi Fans Club Radio Mersi Fm 93.90) - Siti Qonaah; Marlinda Irwanti Poernomo; Frengki Napitupulu (Cakrawala - Jurnal Humaniora, 2022)
Abstract -The disinformation of covid 19 in the media gives a different message for people. A different message affects the audiences of Mersi Radio Fans Club. It is done in order to give the accurate and trusted sources of information related to covid 19. The information can be given through community service announcements disinformation covid version. Based on the problems, the objectives of the research are to describe to the audiences about the true information about covid 19, the influences of different message, the reaction of Mersi Radio Fans Club interpret a message of covid 19 disinformation version, and the factors affect the Mersi Radio Fans Club.  The qualitative research method and the theory of encoding decoding people from Stuart Hall were used to conduct the research.  The theory of decoding was done by the audiences through three positions; they are the hegemony of the dominant position, negotiation position, and opposition position. The result of the research indicated that 5 informants are the most dominant hegemonic position.keyword : reception analysis. encoding decoding